IMPLEMENTASI BLOCKING INTERNET BERBASIS SCHEDULE MIKROTIK UNTUK MENCEGAH DISTRAKSI SISWA DI SMK MA’ARIF PURBOLINGGO - Pratama, Heri; Sutomo, Budi (Jurnal informasi dan komputer, 2023)
The internet technology has a great influence in human's life, including in the education field. In educational institutions, internet technology can be used to support teaching-learning process but also can be a distraction for students. Implementation of internet access blocking in educational institutions has become an important topic in the education world today. Access blocking can be used to control students' internet activities during class hours, reducing distractions and improving learning. In this research, we implement the internet access blocking using Mikrotik Router-based Scheduler in SMK Ma'arif Purbolinggo. We evaluate the effectiveness of the blocking by measuring students' internet access level before and after implementation and conducting surveys to the students and teachers to get feedback on this implementation. The results show that the internet access blocking using Mikrotik can effectively control students' internet activities and improve learning at SMK Ma'arif Purbolinggo.